Evaluation of intimate partner violence vic-tims and perpetrators: A sample from Turkey - Tokgozlu, Omer; Sehlikoglu, Kerem; Bork, Turgay; Turkoglu, Abdurrahim (Klinik Psikiyatri Dergisi, 2024)
Objective: Intimate partner violence (IPV) refers to behaviours such as physical, psychological or sexual harm that occur in close or romantic relationships. The main objectives of this study are to describe the characteristics of IPV victims and perpetrators in Turkey, to elucidate the causes and risk factors associated with IPV, and to discuss the data obtained with similar studies. Method: The study population comprised IPV cases who had consented to participate between February 2019 and June 2020 in the emergency department and forensic medicine clinic. Results: Physical violence emerged as the primary manifestation of IPV, accounting for 98.4% of reported incidents between partners. Jealousy (38.6%) and economic factors (37.6%) were identified as the most common triggers. Of the victims, 204 (65.6%) cases acknowledge this circumstance when exposed to IPV. As the level of education of the victim increases, violence due to jealousy and family factors was observed. The rate of exposure to economic violence was found to be high among women with low income levels. Discussion: It was thought that increasing the level of education of female victims of violence, promoting awareness of violence, fully integrating them into the workforce and thereby securing a sustainable economic income can significantly reduce the incidence of IPV and its acceptance. The study suggests that the widespread implementation of psychological support practices, including premarital education programmes and family counselling focused on addressing issues related to jealousy, holds the potential for substantial benefits in reducing IPV.
Keywords: Intimate partner violence; domestic violence; physical violence; risk factors; sexual violence; perpetrators